Phenolic Constituents from the Twigs of Euonymus alatus and Their Cytotoxic and Anti-inflammatory Activity - Kim, Ki Hyun; Ha, Sang Keun; Choi, Sang Un; Kim, Sun Yeou; Lee, Kang Ro (Planta Medica, 2013)
A bioassay-guided fractionation and chemical investigation of the MeOH extract of the twigs of Euonymus alatus resulted in the isolation and identification of five new phenolic compounds, named alatusols A−E (1–5), together with six known compounds (6–11). The structures of these new compounds were elucidated through spectral analysis, including extensive 2D-NMR data, and their absolute configurations were determined by the modified Mosherʼs method. Compounds 1–3 and 7–9 showed consistent cytotoxicity against A549, SK-OV-3, SK-MEL-2, and HCT-15 cell lines with IC50 values of 15.20–29.81 µM. In addition, compounds 5 and 7 inhibited nitric oxide production in lipopolysaccharide-activated BV-2 cells with IC50 values of 22.77 and 32.52 µM, respectively.
Keywords: Euonymus alatus; Celastraceae; phenylglycerol derivatives; cytotoxicity; anti-neuroinflammation